Educação ambiental e a práxis docente : analisando a TV multimídia no contexto escolar - Sanches, Denise Godoi Ribeiro (2012)
To understand the focus of environmental education with the technology of teaching resources in this research, contextualize the relationship between science, technology and society (STS) and Environmental Education. Elucidate aspects of the discussions that led to the emergence of these perspectives and how environmental education entered in this movement. We emphasize environmental education in basic education and teacher training. Within the school, such activities can be developed with the help of audiovisual and technological feature, present in the public schools of the State of Paraná, TV Multimedia. Thus, there was support in the theoretical references on technology and educational technology, specifically the TV Multimedia. This study sought to examine the effectiveness of environmental education through TV Multimedia educational resource in a public college in the state of Parana. The methodology chosen for this study is qualitative and makes use of technical and methodological procedures that consisted of semi-structured interviews and documentary research. We used to unveil the survey data to content analysis according to Bardin's referential (2010) and Veiga (1995, 1998) specifically for the documentary analysis of the Basic Education Curriculum Guidelines of the State of Paraná, the Pedagogical Political Project College Plans and Work of Teachers. We conclude that environmental issues are not included in all basic education curriculum guidelines of the state of Paraná (DCE), there is emphasis on the disciplines of art, biology, physical education, philosophy, geography, chemistry and sociology. In the Pedagogical Political Project of the college's emphasis on environmental education in the same disciplines and the DCE is the inclusion of several projects related to environmental issues, including for the purpose of enhancement of the local community. For plans of work teachers analyzed the environmental issue is mentioned in the disciplines of art, biology, philosophy, geography, history, English, Portuguese, chemistry and sociology, including some that are not on DCE. Compared with the interviews we believe that these teachers are aware of the obligation of developing environmental education in basic education and have the TV Multimedia as a teaching resource. The interviewed teachers develop activities related to environmental education in their practice in accordance with their capabilities and knowledge of the subject in their areas.